PENGARUH RETURN ON ASSET, DEBT TO EQUITY RATIO, DAN EARNING PER SHARE, TERHADAP RETURN SAHAM PADA PERUSAHAAN LQ45 DI BURSA EFEK INDONESIA PERIODE 2017-2020 - Siregar, Esra Rapma; Silalahi, Donalson (LPPM Universitas Katolik Santo Thomas Medan, 2022)
This study aims to examine and explain the effect of return on assets, debt to equity ratio and earning per share on stock returns in companies including LQ-45 on the Indonesia Stock Exchange for the 2017-2020 period. The population in this study were 45 companies. The sampling technique used is purposive sampling, in order to obtain 9 manufacturing companies. The data analysis technique used is multiple linear regression analysis and uses T test and F test with a significance level of 5 percent. The results showed that return on assets had a positive and significant effect on stock returns, debt to equity ratio had a positive and significant effect on stock returns, Earning per share had a positive and insignificant effect on stock returns. The ability of return on assets, debt to equity ratio and earning per share in explaining variations in stock returns is 31.6 percent